Comparing the performance of urine and copro-antigen detection in evaluating Opisthorchis viverrini infection in communities with different transmission levels in Northeast Thailand. - Chanika Worasith; Chompunoot Wangboon; Kunyarat Duenngai; Nadda Kiatsopit; Kulthida Kopolrat; Anchalee Techasen; Jiraporn Sithithaworn; Narong Khuntikeo; Watcharin Loilome; Nisana Namwat; Puangrat Yongvanit; Elizabeth J Carlton; et al. (Public Library of Science (PLoS), 2019)
To combat and eventually eliminate the transmission of the liver fluke Opisthorchis viverrini, an accurate and practical diagnostic test is required. A recently established urine antigen detection test using monoclonal antibody-based enzyme-linked-immunosorbent assay (mAb-ELISA) has shown promise due to its high diagnostic accuracy and the use of urine in place of fecal samples. To further test the utility of this urine assay, we performed a cross sectional study of 1,043 people in 3 opisthorchiasis endemic communities in northeast Thailand by applying urine antigen detection together with copro-antigen detection methods. The quantitative formalin-ethyl acetate concentration technique (FECT) was concurrently performed as a reference method. The prevalence of O. viverrini determined by urine antigen detection correlated well with that by copro-antigen detection and both methods showed 10-15% higher prevalence than FECT. Within the fecal negative cases by FECT, 29% and 43% were positive by urine and copro-antigen detection, respectively. The prevalence and intensity profiles determined by antigen detection and FECT showed similar patterns of increasing trends of infection with age. The concentration of antigen measured in urine showed a positive relationship with the concentration of copro-antigen, both of which were positively correlated with fecal egg counts. The data observed in this study indicate that urine antigen detection had high diagnostic accuracy and was in concordance with copro-antigen detection. Due to the ease and noninvasiveness of sample collection, the urine assay has high potential for clinical diagnosis as well as population screening in the program for the control and elimination of opisthorchiasis.